Combining zinc oxide nanoparticles with green and novel nanocomposites for enhanced oil recovery in porous media by considering asphaltene deposition and production parameters - Meysam Hemmati; Yaser Ahmadi (Journal of Petroleum Exploration and Production Technology)
Abstract Enhanced oil recovery in depleted, heavy oil, and asphaltene reservoirs has been known as an important matter among researchers. One enthusiastic enhanced oil recovery technique is nano-flooding, where considerable reduction in contact angle and interfacial tension at oil/water interfaces can favorably displace water with oil production from reservoirs. In this research, there is an attempt to review the application of zinc oxide nanoparticles for interfacial tension, contact angle reduction, and inhibiting asphaltene deposition. Because nanoparticles require less concentration of nanocomposites than conventional chemical enhanced oil recovery technologies, working with them is safer and more affordable. The zinc oxide nanoparticles with their small sizes can transport easier through reservoir porous media, and modifying mainly includes wettability alteration, interfacial tension reduction, changing disjoining pressure, emulsification, and preventing asphaltene molecules from aggregation that all help more oil recovery. In this study, recent advances in novel and green nanocomposites combined with zinc oxide for asphaltene deposition and enhanced oil recovery scenarios were reviewed. Results exhibited zinc oxide nanoparticles can reduce interfacial tension and contact angle dramatically and prevent asphaltenes from deposition. In some cases, zinc oxide nanoparticles caused a 93.6% decrease (lowering from 31.8 mN/m to 2.016 mN/m) in interfacial tension and 82.6% decrease (lowering from 161° to 28°) in contact angle that led to displacing water and improving the flow of oil toward production wells. The performance of zinc oxide nanofluids in enhanced oil recovery techniques has not been thoroughly studied before, but our attempt aims to provide light on how zinc oxide may boost oil recovery by altering reservoir properties. Zinc oxide nanoparticles can disperse asphaltene molecules and prevent asphaltene deposition by near 12 wt.%. More than 83% oil recovery can be achieved by zinc oxide nanoparticles flooding.